2011
DOI: 10.1007/s13233-011-0916-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly polarized anatase TiO2 nanoparticles by poly(ethylene phthalate)

Abstract: Highly positively polarized anatase TiO 2 nanoparticles were prepared through the strong interactions between a TiO 2 surface and the phthalate oxygens of poly(ethylene phthalate) (PEP) without stabilizers or surfactants. The prepared anatase TiO 2 nanoparticles were monodisperse with a mean diameter of 55 nm, as confirmed by transmission electron microscopy (TEM) and X-ray diffraction (XRD). Surprisingly, X-ray photoelectron spectroscopy (XPS) showed that the prepared anatase TiO 2 nanoparticles stabilized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Chae et al also observed, in the case of TiO 2 nanoparticles, significant BE changes for Ti 2p 3/2 that were interpreted as interactions in oxygen environments, leading to positive polarizability of Ti–O bonding. The authors anticipated an increase in energy conversion efficiency for modified TiO 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chae et al also observed, in the case of TiO 2 nanoparticles, significant BE changes for Ti 2p 3/2 that were interpreted as interactions in oxygen environments, leading to positive polarizability of Ti–O bonding. The authors anticipated an increase in energy conversion efficiency for modified TiO 2 …”
Section: Resultsmentioning
confidence: 99%
“…The authors anticipated an increase in energy conversion efficiency for modified TiO 2 . 56 Figure 4b,d,f shows XP lines for O 1s regions for p-Ti, NT-Ti, and Ag-NT-Ti, respectively. These regions depict components at 529.79 to 530.31 eV typical of metal oxides (named O/ MeO x ), 531.00 to 531.55 eV corresponding to hydroxylated species (O/−OH) or O/X−O, where X may be P, N, etc., and 532.15 to 532.88 assigned to the oxygen signal from physisorbed water (O/H 2 O).…”
Section: Cyclic Voltammetry (Cv)mentioning
confidence: 99%
“…Among these different methods for the grounding of thin TiO 2 electrochromic layer, sol gel method has numerous advantages mostly the opportunity to produce large surfaces. Besides, sol-gel route also regarded as a good process to create ultra-fine metallic oxide [9] .Moreover, this method has been extensively employed for preparing titanium dioxide particles [10]. So far for the similar route, using different amount of the starting materials the powder size obtained is changed [11] .Sol-gel processes is the low cost methods [12], as well as dip or spin-coating as the last step of preparation .…”
Section: Introductionmentioning
confidence: 99%